Periodontal status of a given population of West Bengal: An epidemiological study - Debabrata Kundu; Ritesh Mehta; Shallu Rozra (Wolters Kluwer Medknow Publications, 2011)
Background: This paper presents the prevalence and severity of periodontal disease in a given population of West Bengal and its relationship with their age, sex, socioeconomic status, educational background, and dietary habits. Also, the treatment needs on the basis of Community Periodontal Index of Treatment Needs (CPITN), which might be helpful for future planning of dental services. Materials and Methods: A sample of 22,452 individuals aged 15 years and above was selected using a random cluster sampling from the population. All the subjects sampled were weighed by age, sex, community, income group, educational level, diet pattern, and habitation. The WHO CPITN was used to assess the levels of periodontal condition and treatment needs. Results: Score 2 was most prevalent in all the groups. Periodontal disease is widespread in West Bengal and a positive relation appears to exist between age, sex, socio-economic status, education level, and dietary habits with periodontal status. Comprehensive oral hygiene instruction and dental prophylaxis need to be initiated. Conclusion: The data on periodontal conditions presented in this study are similar to data available from WHO on global oral health. These estimates are important for the future planning of dental services in the state.